Gender disparities in mortality from infectious diseases in Serbia, 1991–2014: a time of civil wars and global crisis. Issue 12 (22nd June 2016) - ILIC, M.; ILIC, I.
SUMMARY: Infectious diseases remain one of the leading causes of death worldwide. The aim of this descriptive epidemiological study was to analyse the trends in mortality from infectious diseases in Serbia (excluding the Autonomous Province of Kosovo & Metohia) from 1991 to 2014 using joinpoint regression analysis. The mortality rates from infectious diseases were found to have increased markedly from 1991 to 1994 (+12·4% per year), followed by a significant decline from 1994 to 2009 (–4·6% per year) and then another increase from 2009 to 2014 (+4·3% per year). Throughout the study period, mortality rates were consistently higher in men than in women. Although a substantial decline was observed for young people of both sexes, no consistent pattern was evident for the middle-aged nor the elderly. Since 1991, septicaemia has emerged as a leading cause of infectious disease mortality, particularly in older men. The Yugoslav civil wars in the 1990s and the global financial crisis in 2008 corresponded with changes in the trends in mortality from infectious diseases in Serbia, with the elderly showing particular vulnerability during those time periods. Data presented in this study might be useful to improve control of infectious diseases in Serbia.